Time and position aware resource search algorithm for the mobile peer-to-peer network using ant colony optimisation. (25th August 2022) - Kumar, Dharmendra; Dubey, Ajay Kumar; Pandey, Mayank
The progressive growth of wireless mechanisms and the wide popularity of intelligent devices are attracting particular attention to peer-to-peer mobile ad hoc networks (P2P MANET). Increasing the efficiency to search the resources became an important research topic in the P2P MANETs. Most existing research gives more emphasis on position-based clustering techniques and does not give preference to time. Due to not giving any preference to time, the existing approaches are not so appropriate to improve the efficiency to search the resources in P2P MANETs. This paper suggests a navel resource search approach that first uses position-aware peer clustering strategy. Then, using an ant colony optimisation method with pheromones, it chooses the preeminent neighbour's peer that is of time-aware neighbouring peer's resource preferences and the time-aware neighbouring peer's availability. Based on the results of the experiment, this approach outweighs other approaches in terms of search delay, overhead traffic, and search success rate.